Studi Penggunaan Omeprazole pada Pasien Sirosis Hati dengan Hemetamesis Melena Rawat Inap di RSUD Kabupaten Sidoarjo - Wiranata, I Made; Hasmono, Didik; Surdijati, Siti (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
Liver cirrhosis is a process of liver cell damage which later becomes fibrosis tissue. Then, the occurrence of liver structural distortion and increased vascularization to the liver resulting in varicose veins or dilation of blood vessels in the gastrointestinal and esophageal areas. Patients with esophageal varices, there is a risk of bleeding from esophageal rupture, the undergone hematemesis (vomiting of blood) and melena (blackish defecate). The therapies used to reduce gastrointestinal bleeding are gastric ulcers drugs such as H2Ras and PPI. The study aimed to determine the pattern of omeprazole use in liver cirrhosis patients with hematemesis melena. The method used was an observational retrospective study in medic record data patients. Sampling was done by consecutive sampling, the period of Juli 1, 2015 until Descember 31, 2015. The results obtained from the study were single use of omeprazole with a dose of 2x40mg/i.v used the most by 22 patients (73.3%). The use of omeprazole with a dose of 2x40mg/i.v combined with other gastric ulcer drugs was 7 patients (23.3%), omeprazole with ranitidin 6 patients, omeprazole with antacid for 1 patient. The use of omeprazole with a dose of 2x40mg was replaced with ranitidin 2x25mg/ml was 1 patient (3.3%). The use of omeprazole given in liver cirrhosis patients with hematemesis melena at the Inpatient Installation of Regional Hospital of Sidoarjo, related dose, route, frequency, interval, and duration of giving was in appropriate with the guidelines contained in the National Formulary.